Mortgage equity withdrawal and institutional settings: An exploratory analysis of six countries - Haffner, M.; Ong, Rachel; Wood, Gavin (Routledge, 2015)
In this exploratory paper, we investigate whether there are links between institutional context and the development of markets in home equity conversion that are based on financial instruments facilitating mortgage equity withdrawal (MEW). Using secondary data and literature sources from six countries (Australia, UK, USA, Netherlands, Finland and Germany), the paper addresses two research questions. First, to what extent are there differences in the range and use of MEW financial instruments across these six countries? Second, how might the institutional context governing a nation's housing and capital markets support or hinder MEW in these countries? The paper concludes by drawing some implications for debates sparked by housing's changing welfare role as a means of smoothing consumption over the life cycle.